Effects of cryopreservation on performance and fertilizing ability of sperm from Kerai (Puntius daruphani) - Emhemed, Mohamed M. M. (2008)
Puntius daruphani broodstocks bought from fishermen in Temerloh, Pahang, conditioned in the Hatchery Unit of Universiti Putra Malaysia were used for all the experiments. In this study fresh and cryopreserved sperm of P. daruphani were analyzed for their physical characteristics (motility, motile period, live sperm count and abnormality), morphology, fertilizing ability and hatching rate. Kurokura medium and dimethyl sulfoxide (DMSO) were used as extender and cryoprotectant, respectively in the cryopreservation of the sperm. The percentage of motility, live sperm count and time of motile period after activation of frozen-thawed sperm were significantly lower than that of fresh sperm. Whereas the percentage of abnormality for frozen-thawed sperm was significantly higher than fresh sperm. ANOVA showed that there was no significant different (p>0.05) between fresh samples for all the parameters, whereas results among frozen-thawed samples using different concentrations of DMSO (10 - 15%) were significantly different (p<0.05) for all the parameters. Results of fertilizing ability and hatching rate were significantly different (p<0.05) between fresh and cryopreserved samples, whereas there were no significant different (p>0.05) among frozen-thawed samples. The entire testis with total length ranged from 9.8 to 11.3cm, were categorized as the anterior, middle and posterior parts. The anterior, middle and posterior parts were creamy in colour and having soft tissue. Anterior and middle parts involved in the production of spermatozoa. Posterior part as glandular testis is only displayed some ducts with smooth muscle layer and produce seminal fluids. P. daruphani sperm consisted from three parts head, midpice and flagellum, measuring 2.19±0.01, 0.955±0.02 and 17.08±0.05 μm respectively. In the first experiment, the results on the physical characteristics (motile period, motility, abnormality and live sperm count) were significantly different (p<0.05) between the fresh and cryopreserved sperm (using 10% DMSO as cryoprotectant). However the results between 1 and 3-month cryopreserved sperm samples were significantly different (p<0.05) for all the above parameters. Liquid nitrogen affected the sperm membrane function and mitochondria, increased the percentage of abnormality by damaging the cells of the spermatozoa. In the second experiment, the results on the physical characteristics (motile period, motility, abnormality and live sperm count), fertilizing ability and hatching rates were significantly different (p<0.05) between the fresh and cryopreserved samples of 1 and 3-month (using 15% DMSO). There were no significant different (p>0.05) between the cryopreserved sperm samples of 1 and 3-month for all the parameters above. However, there were significant different (p<0.05) for all the physical characteristics (motile period, motility, abnormality and live sperm count) between cryopreserved (1 and 3 month) sperm samples using 10 and 15% DMSO. These results are supported by the observation on the sperm morphology showing that by using 15% DMSO produced less damages on the sperm membrane, cytoplasmic mitochondria and flagellum as compared to 10% DMSO.